The art of Richard Diebenkorn - Livingston, Jane (University of California Press, 1997)
Richard Diebenkorn (1922-1993) quietly constructed a place for himself in the history of twentieth-century art with his singular vision and intense commitment to the idea and practice of both figuration and abstraction. In this book, which accompanies the Whitney Museum's 1997 Diebenkorn retrospective exhibition, the most comprehensive survey of his work ever held, Diebenkorn emerges as an artist who restored to late modernism the sense of the sublime that seemed to fade with each successive decade after World War II. In the 1940s and early 1950s, he forged an impressive abstract vocabulary - and then suddenly abandoned it in 1955 for a representational mode that encompassed still lifes, landscapes, figures, and interiors. Along with painters David Park and Elmer Bischoff, he established what has come to be known as the Bay Area Figurative School. Twelve years later, in 1967, Diebenkorn moved back into abstraction, embarking on the renowned Ocean Park series of paintings and drawings that he continued to develop until the end of his life.